Erdafitinib inhibits the tumorigenicity of MDA-MB-231 triple-negative breast cancer cells by inducing TRIM25/ubiquitin-dependent degradation of FGFR4 - Qing Luo; Li Zhang; Yue Hao; Chunwei Xu; Xiaojia Wang; Zhen Jia; Xiandong Xie; Zhihong Huang; Xiaomin Gao; Yu Chen; Xue Zhu; Jing Fang; et al. (Breast Cancer Research)
Abstract Triple-negative breast cancer (TNBC) is the most malignant subtype of breast cancer (BC), characterized by limited treatment options and poor clinical outcomes. Aberrant FGFR signaling has been implicated in TNBC; however, the therapeutic potential of targeting FGFRs for TNBC treatment remains unclear. This study investigated the anti-cancer activity of the selective pan-FGFR inhibitor Erdafitinib and its underlying mechanisms using both in vitro and in vivo models. The results demonstrated that Erdafitinib suppressed TNBC tumorigenicity by promoting FGFR1/4 degradation, generating reactive oxygen species (ROS), inducing DNA damage, and ultimately triggering cell death. Mechanistic analyses revealed that Erdafitinib facilitated FGFR1/4 degradation through ubiquitination, enhanced interaction between TRIM25 and FGFR1/4, and subsequent lysosomal degradation. Furthermore, RNA-seq data from the TCGA and GEO databases, along with paired tumor tissues from TNBC patients, indicated that FGFR4 was significantly upregulated in TNBC. Notably, co-knockdown of FGFR1 and FGFR4 induced cytotoxicity in MDA-MB-231 cells, highlighting the therapeutic relevance of FGFR1/4 degradation by Erdafitinib in TNBC. These findings provide novel insights into the mechanisms underlying the anti-cancer efficacy of Erdafitinib, supporting its potential as a promising therapeutic agent for TNBC.